👤

Efectuați calculele:
[tex]2 \sqrt{3} \times ( \sqrt{5} - 1)( \sqrt{5} + 1) + (2 \sqrt{3} - 5) {}^{2} + (3 \sqrt{3} + 2) {}^{2} = [/tex]


Răspuns :

[tex]2 \sqrt{3} \times ( \sqrt{5} - 1)( \sqrt{5} + 1) + (2 \sqrt{3} - 5) {}^{2} + (3 \sqrt{3} + 2) {}^{2} = \\ [/tex]

Îl fac pe bucățele

[tex]( \sqrt{5} - 1)( \sqrt{5} + 1) = \sqrt{5} {}^{2} - {1}^{2} = \\ = 5 - 1 = 4[/tex]

[tex](a + b)(a - b) = a {}^{2} - b {}^{2} [/tex]

[tex](2 \sqrt{3} - 5) {}^{2} = 4 \times 3 - 20 \sqrt{3} - 25 = \\ = 12 - 20 \sqrt{3} + 25[/tex]

[tex](a - b) {}^{2} = a {}^{2} - 2ab + b {}^{2} [/tex]

[tex](3 \sqrt{3} + 2) {}^{2} = 9 \times 3 + 12 \sqrt{3} + 4 = \\ = 27 + 12 \sqrt{3} + 4[/tex]

[tex](a + b) {}^{2} = a {}^{2} + 2ab + b {}^{2} [/tex]

Le punem pe toate la un loc

[tex] = 2 \sqrt{3} \times 4 + 12 - 20 \sqrt{3} + 25 + 27 + 12 \sqrt{3} + 4 = \\ = 8 \sqrt{3} - 20 \sqrt{3} + 12 \sqrt{3} + 12 + 25 + 27 + 4 = \\ = 12 + 25 + 27 + 4 = \\ \huge = 68[/tex]

(Dacă ești pe telefon și nu vezi tot glisează spre dreapta.)